Growth of freshwater cyanobacterium Aphanizomenon sp. ULC602 in different growing and nutrient conditions - Pham, Mai-Lan; Askarzadmohassel, Elahe; Brandl, Martin (Frontiers in Microbiology, 2023)
Aphanizomenon sp. ULC602, recently isolated in a Belgian lake, is a filamentous, nitrogen-fixing, freshwater cyanobacterium that is one of the primary producers of cyanotoxins following its bloom-formation, causing water contamination. The aim of this study is to evaluate the effects of growing conditions and essential nutrients on the growth of Aphanizomenon sp. ULC602 via its production of chlorophyll-a (Chlo-a). Our results indicated that this bacterium could grow well at temperatures ranging from 18-25 °C with an optimal pH from 6.0-7.5 under continuous lighting. It still grew slowly in the absence of a carbon source or at lower concentrations. The addition of nitrogen from nitrate and urea made a less than 50% reduction of Chlo-a content compared to the medium lacking nitrogen. The iron bioavailability significantly stimulated the Chlo-a production, but it was saturated by an iron concentration of 0.115 mM. Moreover, a decrease of Chlo-a biomass was observed under the sulphur deficiency. The bacterium could not grow well in all media containing various phosphorus sources. In conclusion, as the growth and consequent forming bloom of cyanobacteria can be stimulated or inhibited by environmental conditions and eutrophication, our investigation could contribute to further studies to control the blooming of the target bacterium in freshwater.